The Generation of an Engineered Interleukin-10 Protein With Improved Stability and Biological Function - Minshawi, Faisal; Lanvermann, Sebastian; McKenzie, Edward; Jeffery, Rebecca; Couper, Kevin; Papoutsopoulou, Stamatia; Roers, Axel; Muller, Werner (Frontiers in Immunology, 2020)
Interleukin-10 (IL-10) is an immunoregulatory cytokine that plays a pivotal role in modulating inflammation. IL-10 has inhibitory effects on proinflammatory cytokine production and function in vitro and in vivo; as such, IL-10 is viewed as a potential treatment for various inflammatory diseases. However, a significant drawback of using IL-10 in clinical application is the fact that the biologically active form of IL-10 is an unstable homodimer, which has a short half-life and is easily degraded in vivo. Consequently, IL-10 therapy using recombinant native IL-10 has had only limited success in the treatment of human disease. To improve the therapeutic potential of IL-10, we have generated a novel form of IL-10, which consists of two IL-10 monomer subunits linked in a head to tail fashion by a flexible linker. We show that the linker length per se did not affect the expression and biological activity of the stable IL-10 molecule, which was more active than natural IL-10, both in vitro and in vivo. We confirmed that the new form of IL-10 had a much-improved temperature- and pH-dependent biological stability compared to natural IL-10. The IL-10 dimer protein binds to the IL-10 receptor similarly to the natural IL-10 protein, as shown by antibody blocking and through the genetic modifications of one monomer in the IL-10 dimer specifically at the IL-10 receptor binding site. Finally, we showed that stable IL-10 is more effective at suppressing LPS-induced-inflammation in vivo compared to the natural IL-10. In conclusion, we have developed a new stable dimer version of the IL-10 protein with improved stability and efficacy to suppress inflammation. We propose that this novel stable IL-10 dimer could serve as the basis for the development of targeted anti-inflammatory drugs.